Specificity of Saliva Esterases by Wine Carboxylic Esters and Inhibition by Wine Phenolic Compounds Under Simulated Oral Conditions - Pérez-Jiménez, María; Muñoz-González, Carolina; Pozo-Bayón, María Ángeles (Frontiers in Nutrition, 2021)
The specificity of human esterase activity (EA) from stimulated (SS) and non-stimulated (NSS) saliva towards different typical wine odorant carboxylic esters and its inhibition by wine phenolic compounds has been evaluated. For the specificity, six p-nitrophenyl linked esters with different carbon chain length (from 2 to 12 carbons) was employed. Five single phenolic compounds (catechin, quercetin, kaempferol, myricetin and resveratrol) at typical wine concentrations were assayed in the salivary EA inhibition study. Additionally, the inhibition exerted by mixtures of wine polyphenols was also evaluated using four commercial phenolic extracts (a grape seed extract, the monomers and oligomer fraction of the grape seed extract and a red wine extract). Finally, the saliva EA under wine consumption conditions (pH = 5 and 11.3% ethanol) was also evaluated. The results showed a higher EA in stimulated than unstimulated saliva. It was also shown that EA was higher towards smaller than bigger esters regardless the saliva types (SS, NSS). On the other hand, the inhibition exerted on saliva EA by individual and mixtures of phenolic compounds was proven. Catechin was the phenolic compound which most inhibited saliva EA, while resveratrol showed the lowest EA inhibition. This inhibition was mainly related to the concentration of the phenolic compounds, but also with its structure. Finally, under simulated wine consumption, a decrease in EA was produced, which was mainly provoked by the decrease in salivary pH. Nonetheless, since salivary pH recovers a few seconds after wine consumption, saliva EA might be relevant for the long lasting perception of wine esters.